Terrains, complexes and provinces in the central cordillera of Colombia (2009)
The Central Cordillera of Colombia consists of several tectonostratigraphic terrains that have not been fully recognized yet. To the east of San Jerónimo Fault are found the Chibcha, Tahamí, Panzenú (Puquí) and Anacona (Caldas) terrains with continental basement, and between the Romeral and the Cauca fault systems the Quebradagrande, Amagá-Sinifaná, Heliconia and Arquía terranes, mostly oceanic, are found. The Chibcha terrain is formed by a Grenvillian basement covered by Lower Paleozoic sediments that suffered a slight metamorphism, while in the Tahamí the metamorphism is Late Permian to Triassic, indicating that it was formed within the collision zone of Pangea but rather in the Paleopacific margin of Pangea as part of the Terra Australis Orogen. The metamorphism in the Panzenú Terrain is somewhat older, Carboniferous. The Anacona Terrain presents Devonian metamorphism and was not affected by the Triassic metamorphism that affected the Tahamí, indicating that it had not been amalgamated yet during the Triassic orogeny. A number of narrow belts of allochtonous rocks were accreted after Mid-Cretaceous times to the Tahamí Terrane which are from east to west: the Quebradagrande Complex, the Sinifaná low-grade metasedimentary rocks and the Amagá Granite (Amagá-Sinifaná Terrane), the ophiolitic rocks of Heliconia and the Arquía Complex. All of them are located between the systems of faults Cauca and Romeral.